2018
DOI: 10.1152/ajprenal.00569.2017
|View full text |Cite
|
Sign up to set email alerts
|

Divergent roles for kidney proximal tubule and granulocyte PAD4 in ischemic AKI

Abstract: We previously demonstrated that kidney peptidylarginine deiminase-4 (PAD4) plays a critical role in ischemic acute kidney injury (AKI) in mice by promoting renal tubular inflammation and neutrophil infiltration (Ham A, Rabadi M, Kim M, Brown KM, Ma Z, D'Agati V, Lee HT. Am J Physiol Renal Physiol 307: F1052-F1062, 2014). Although the role of PAD4 in granulocytes including neutrophils is well known, we surprisingly observed profound renal proximal tubular PAD4 induction after renal ischemia-reperfusion (I/R) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…We have previously shown that renal I/R injury induced renal proximal tubular PAD4 synthesis and activity (22,49). Our studies linked both renal proximal tubular as well as leukocyte PAD4 to critical roles in ischemic AKI as mice deficient in renal proximal tubular PAD4 as well as leukocytederived PAD4 were protected against ischemic AKI (40).…”
Section: Discussionmentioning
confidence: 60%
“…We have previously shown that renal I/R injury induced renal proximal tubular PAD4 synthesis and activity (22,49). Our studies linked both renal proximal tubular as well as leukocyte PAD4 to critical roles in ischemic AKI as mice deficient in renal proximal tubular PAD4 as well as leukocytederived PAD4 were protected against ischemic AKI (40).…”
Section: Discussionmentioning
confidence: 60%
“…Further studies are required to explore the function of PAD4 in human lupus nephritis. In addition, the role of PAD4 in neutrophils and renal proximal tubular cells has been reported in acute kidney injury (61). Therefore, future studies with conditional KO mice specific for either neutrophils or tubular cells are also needed to dissect the cell-specific effect of PAD4 in lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…M2-activated macrophages are comprised of wound healing and immunoregulatory macrophages (Shapouri-Moghaddam et al 2018). M2 macrophages secrete resolvins, lipoxins, transforming growth factor beta, and matrix metalloproteinases to cleave chemokines and chemoattractants and suppress the inflammatory response, contribute to tissue repair, remodeling, vasculogenesis, and retain homeostasis (Han et al 2018; Shapouri-Moghaddam et al 2018). M-CSF is a hematopoietic growth factor responsible for the survival and proliferation of monocytes and the differentiation of monocytes into macrophages (Radi et al 2011).…”
Section: The Immune and Renal Systems Network And Cross Talksmentioning
confidence: 99%
“…Peptidylarginine deiminase-4 (PAD4) plays a critical role in ischemic AKI in mice by promoting renal tubular inflammation and neutrophil infiltration (H. Li et al 2018). Renal proximal tubular cell in PAD4 deficient mice had profoundly reduced renal tubular apoptosis (H. Li et al 2018). Although neutrophil infiltration can be noted in the kidney following ischemic injury in I/R injury animal models (Nemoto et al 2001; Tadagavadi et al 2015) and human biopsies of AKI patients (Solez, Morel–Maroger, and Sraer 1979; Friedewald and Rabb 2004), neutrophil depletion and neutropenia in rats did not protect against ischemic injury (Paller et al 1989).…”
Section: The Immune and Renal Systems Network And Cross Talksmentioning
confidence: 99%
See 1 more Smart Citation